Community Empowerment Program by PT Pertamina Patra Niaga DPPU Ngurah Rai: Efforts to Respond to the Environmental Crisis Through the Eco-Religion Waste Management System in Kedonganan Traditional Village, Bali - Putri Kinasih E A A J; Muhammad Saghar Septian; Erly Yeniska Hermitasari; Farka Alfa Centauri (Prospect: Jurnal Pemberdayaan Masyarakat, 2023)
This paper seeks to explain the community empowerment program carried out by PT Pertamina Patra Niaga DPPU Ngurah Rai as a commitment in implementing CSR. The community empowerment CSR program is called Eco-Religion Waste Management System Kedonganan Ngardi Resik. The background of the development of this program, namely: the preservation of customs and culture of the community in Kedonganan Traditional Village Bali. The community there conducts prayer activities through canang facilities made of â€œjanurâ€ as an expression of gratitude to Him. After the worship is over, the canang is forced to become a residue that is disposed of in the landfill because the community is not used to sorting waste from the smallest scale. This community empowerment program was developed through the Logical Framework Approach (LFA) model in responding to environmental crises carried out with the Kedonganan Traditional Village Bali community by mainstreaming religious, social, and cultural communities to create an integrated waste management system. This program has succeeded in creating a disciplined community in sorting waste from the household level and processing waste into compost and bio charcoal briquettes that are reused by the community. This program also contributes to reducing environmental impact of reducing greenhouse gas emissions.